2014
DOI: 10.1105/tpc.114.129312
|View full text |Cite
|
Sign up to set email alerts
|

A Microbial Avenue to Cell Cycle Control in the Plant Superkingdom    

Abstract: Research in yeast and animals has resulted in a well-supported consensus model for eukaryotic cell cycle control. The fit of this model to early diverging eukaryotes, such as the plant kingdom, remains unclear. Using the green alga Chlamydomonas reinhardtii, we developed an efficient pipeline, incorporating robotics, semiautomated image analysis, and deep sequencing, to molecularly identify >50 genes, mostly conserved in higher plants, specifically required for cell division but not cell growth. Mutated genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
197
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(210 citation statements)
references
References 60 publications
13
197
0
Order By: Relevance
“…This regulatory scheme provides a natural distinction between genes primarily required for cell growth and integrity and genes required specifically for the cell division cycle. We found that the 10-hr and 20-hr time points are very informative for an initial rough phenotypic cut 1 . The broad classes of ts lethal mutants that we recognize currently, based on these images (see S.I.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This regulatory scheme provides a natural distinction between genes primarily required for cell growth and integrity and genes required specifically for the cell division cycle. We found that the 10-hr and 20-hr time points are very informative for an initial rough phenotypic cut 1 . The broad classes of ts lethal mutants that we recognize currently, based on these images (see S.I.…”
Section: Discussionmentioning
confidence: 97%
“…The "Notch" and "Popcorn" phenotypes were shown previously to be characteristic of most cell cycle-specific lesions (e.g., mitotic cyclin-dependent kinase, DNA replication machinery, and Topoisomerase II) 1 . The appearance of one (Notch) or multiple (Popcorn) apparent planes of incipient but unsuccessful cell division is a convenient morphological indicator of cell cycle initiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations